Legal Certainty Regarding the Conversion of Land Certificates To An Electronic System Based On Security Principles - H Holla; Rafi Salhi; Clarissa Oktaviriya Prakoso (Jurnal Ilmu Kenotariatan)
The purpose of this study is to determine the regulation of conversion of land certificate issuance to electronic system, in addition to determine the legal consequences of the security principle of electronic certificates. The type of research uses normative juridical. With the Legislative and conceptual approaches. The results of the study are: 1. That in the issuance of electronic certificates through 2 stages, namely the first issuance of electronic certificates through the first land registration for land that has not been registered, the mechanism is carried out by collecting and processing physical data, proof of rights and bookkeeping, issuance of certificates, presentation of physical data and legal data and storage of general lists and documents carried out through an electronic system. Second is the issuance of replacement certificates from analog certificates to electronic certificates for land that has been registered, replacement is carried out through a request for land registration data maintenance services and replacement is carried out if the physical data and legal data in the land book and certificate are in accordance with those in the electronic system. That the policy of implementing electronic land certificates is an effort to improve land services and ensure legal certainty in an effort to provide legal protection for its owners. The benefits for the community from electronic certificates are that there is guaranteed legal certainty and it reduces land certificate disputes because the electronic certificate security system already uses encryption technology such as cryptography.